Axiom, Anguish, and Amazement: How Autistic Traits Modulate Emotional Mental Imagery - Esposito, Gianluca; Dellantonio, Sara; Mulatti, Claudio; Job, Remo (Frontiers in Psychology, 2016)
Individuals differ in their ability to feel their own and others’ internal states, with those that have more autistic and less empathic traits clustering at the clinical end of the spectrum. However, when we consider semantic competence, we would expect this group to compensate with a higher capacity to imagine the meaning of words referring to emotions. This is indeed what we found when we asked people with different levels of autistic and empathic traits to rate the degree of imageability of various kinds of words. But this was not the whole story. Individuals with marked autistic traits demonstrated outstanding ability to imagine theoretical concepts, i.e. concepts that are commonly grasped linguistically through their definitions. This distinctive characteristic was so pronounced that, using tree-based predictive models, it was possible to accurately predict participants’ inclination to manifest autistic traits, as well as their adherence to autistic profiles – including whether they fell above or below the diagnostic threshold – from their imageability ratings. We speculate that this quasi-perceptual ability to imagine theoretical concepts, coupled with a lowered ability to imagine emotional terms represents a specific cognitive pattern that, while hindering social interaction, may favour problem solving in abstract, non-socially related tasks. This would allow people with marked autistic traits to make use of perceptual, possibly visuo-spatial, information for “higher” cognitive processing.